Exposure of Goniopora columna to polyethylene microplastics (PE-MPs): Effects of PE-MP concentration on extracellular polymeric substances and microbial community. (June 2022) - Hung, Chang-Mao; Huang, Chin-Pao; Hsieh, Shu-Ling; Chen, Ya-Ting; Ding, De-Sing; Hsieh, Shuchen; Chen, Chiu-Wen; Dong, Cheng-Di
Abstract: Although the pollution of coral reefs by microplastics (MPs) is an environmental problem of global significance, the effects of MP concentration on scleractinian corals remain largely underexplored. Herein, we exposed a representative scleractinian coral ( Goniopora columna ) to different concentrations (5–300 mg L −1 ) of polyethylene microplastics (PE-MPs; 40–48 μm) over seven days and evaluated the changes in microbial community and extracellular polymeric substances (EPS) using fluorescence excitation–emission matrix spectroscopy and amplicon sequence variants (ASV). At a PE-MP concentration of 300 mg L −1, the relative abundance of Bacillus ( Firmicutes phylum) and Ruegeria ( Proteobacteria phylum) in PE-MP-associated EPS increased and decreased, respectively, while the effects of exposure depended on the particle size of the extracellular polymeric substance (EPS)-based matrix and the humification index. Humic- and fulvic-like substances were identified as critical EPS components produced by microbial activity. The results have shed new insights into short-term responses of G. columna during exposure to different PE-MP concentrations and reveal important coral-MP-microbiome interactions in coral reef ecosystems. Results demonstrated that the coral-MPs interactions should be further evaluated to gain a deeper understanding of the underlying ecotoxicological risks. Graphical abstract: Image 1 Highlights: Goniopora exposure to microplastics exhibited eco-morphological changes. Goniopora exposure to microplastics affected microbiome/extracellular polymeric substances. ATR-FTIR and FEEM analyses revealed significant changes in cellular structures. Humic- and fulvic-like species were critical extracellular polymeric substances components. Exposure to microplastics increased the abundance of Bacillus relative to that of Ruegeria.